2007
DOI: 10.1007/s10535-007-0160-3
|View full text |Cite
|
Sign up to set email alerts
|

In vitro bud regeneration of Carthamus tinctorius and wild Carthamus species from leaf explants and axillary buds

Abstract: The organogenic competence of leaf explants of eleven Carthamus species including C. tinctorius on Murashige and Skoog (MS) medium supplemented with different concentrations of thidiazuron (TDZ) + -naphthaleneacetic acid (NAA) and 6-benzyladenine (BA) + NAA was investigated. Highly prolific adventitious shoot regeneration was observed in C. tinctorius and C. arborescens on both growth regulator combinations and the shoot regeneration frequency was higher on medium supplemented with TDZ + NAA. Nodal culture of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 13 publications
1
12
0
1
Order By: Relevance
“…This result can be explained with the presence of predetermined cells which first dedifferentiate themselves, subsequently form new meristematic centres, and finally differentiate again producing new organs [34][35][36][37][38][39]. This process, due to cell totipotency, has been observed in several species [30,[40][41][42][43][44][45][46][47] and is very efficient for regeneration. Our results showed that AFLP is a very sensitive and reliable molecular marker technique for revealing specific genomic alterations induced by tissue culture and for identifying slightly different genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…This result can be explained with the presence of predetermined cells which first dedifferentiate themselves, subsequently form new meristematic centres, and finally differentiate again producing new organs [34][35][36][37][38][39]. This process, due to cell totipotency, has been observed in several species [30,[40][41][42][43][44][45][46][47] and is very efficient for regeneration. Our results showed that AFLP is a very sensitive and reliable molecular marker technique for revealing specific genomic alterations induced by tissue culture and for identifying slightly different genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Direct regeneration from leaf, as another alternative step for clonal propagation and germplasm conservation, is a well established factor. Successful plant regeneration has been reported from leaf explants, e.g., in Indian spinach (Mitra and Mukherjee 2001), Plumbago species (Das and Rout 2002), safflower (Radhika et al 2006) and Carthamus species (Sujatha and Dinesh Kumar 2007). In view of the medicinal properties of S. acmella, its threatened nature and the increased demand for it in the pharmaceutical industry, there is a need for a large scale multiplication.…”
mentioning
confidence: 99%
“…In addition, shoot regeneration from nodal segments by direct organogenesis in vitro has not yet been reported for S. nigrum. The cytokinins Kin and ZT (alone or in combination with auxins) are commonly used to induced callus formation and organogenesis in plant tissues (Kou et al 2012;Sujatha & Kumar 2007). In this study, all the cytokinins tested (KIN or ZT) could induced callus from petioles and rooted hypocotyls (Table 1).…”
Section: Discussionmentioning
confidence: 72%